La vie après 50 ans Faits marquants révélés par l'enquête européenne SHARE - Flawinne, Xavier (Presses universitaires de Liège, 2021)
The lengthening of life is at the center of major societal challenges. Whether these challenges concern individual health or general living together, we will all be led to discover the many changes that aging directly or indirectly implies in the lives of everyone. To give some elements of understanding to people who might have questions on this subject, the authors draw on the lessons learned from the European SHARE survey. Since 2004, SHARE has been following cohorts of people aged 50+ in Europe in order to analyze the interactions between different dimensions: family, social relationships, work and retirement, physical and mental health, living conditions, etc. The information collected in the framework of this project has allowed the realization of multiple research studies, many of them interdisciplinary, a selection of which is presented in a popularized manner throughout the twenty chapters of this book. These chapters illustrate the extent to which reality often runs counter to preconceived ideas about aging. Coupled with new insights from the summer 2020 SHARE-COVID, this knowledge becomes even more valuable in understanding the impact that the Covid-19 pandemic will have on the elderly population in European countries. The authors introduce this topic in the 21st chapter of this book. We hope that curious readers will find the information useful for themselves and for those around them.